Analisis Pendapatan Usahatani Tanaman Porang (Amorphophallus Muelleri (Studi Kasus Di Desa Paru Keude Kecamatan Bandar baru Kabupaten Pidie Jaya) - Dhiaul Ariz; Zakiah Hasan; Anwar Deli (Fakultas Pertanian, Universitas Syiah Kuala, 2022)
Porang farming is a profitable farm if cultivated because the price of this porang plant can be said to be high because many other countries are interested in porang and that makes porang prices expensive by exporting to various countries such as Japan, China, Korea, Thailand and many more. country again and it will make the farmers' economy can increase. This study aims to determine the income of porang farmers and how feasible porang farming is in Paru Keude Village, Bandar Baru District, Pidie Jaya Regency. The type of data used in this study is primary data and secondary data, primary data is data that is directly given by respondents using questionnaires. The analytical method used in this study is to use the formula for farmers' income and farming feasibility. The results of the research show that the average income of porang farming in Paru Keude village, Pidie Jaya district, is Rp. 99,185,000 per growing season. Porang farming is feasible because the B/C Ratio obtained from porang farming is much greater than 1, which is 2.7. In the BEP analysis, farmers do not experience profits or losses or break even if the income received by farmers is Rp. 3,775,641/kg, the production obtained is 220.8 kg and the price per kilo porang is Rp. 1,989/kg. Meanwhile, with an area of 1 ha, the average income is Rp. 159,407,000 with a B/C Ratio of 2.8. BEP analysis on an area of 1 Ha, farmers do not experience losses or gains if the income is Rp. 4,633,974/kg. The production obtained is 272.05 kg and the price per kg of porang is Rp. 1,965/kg.